2019
DOI: 10.1038/s41746-019-0126-9
|View full text |Cite
|
Sign up to set email alerts
|

Benchmark on a large cohort for sleep-wake classification with machine learning techniques

Abstract: Accurately measuring sleep and its quality with polysomnography (PSG) is an expensive task. Actigraphy, an alternative, has been proven cheap and relatively accurate. However, the largest experiments conducted to date, have had only hundreds of participants. In this work, we processed the data of the recently published Multi-Ethnic Study of Atherosclerosis (MESA) Sleep study to have both PSG and actigraphy data synchronized. We propose the adoption of this publicly available large dataset, which is at least on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 46 publications
1
85
1
Order By: Relevance
“…Penzel et al provided an in depth review of some of these approaches in clinical settings, offering a quantitative analysis of their performance and requirements 106 . Palotti et al evaluated the performance of some of the most common approaches, including statistical ML, on actigraphy data 107 .…”
Section: Conventional Sleep Classification Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Penzel et al provided an in depth review of some of these approaches in clinical settings, offering a quantitative analysis of their performance and requirements 106 . Palotti et al evaluated the performance of some of the most common approaches, including statistical ML, on actigraphy data 107 .…”
Section: Conventional Sleep Classification Methodsmentioning
confidence: 99%
“…Machine learning and deep learning approaches have gained traction in recent years for the task of classifying sleep-wake cycles and sleep stages in multi-modal sensor data 108,109 . With the availability of raw actigraphy signals, several deep-learning techniques such as convolutional neural networks 110 and recurrent neural networks 111 have been used to exploit the temporal nature of this unstructured data to distinguish the sleep-wake cycles 107 robustly and understand the role of activity in sleeprelated disorders 112 . Whilst the evaluation of most traditional and ML algorithms are performed using standard quality metrics such as accuracy, precision and recall per class, it is also important to measure clinically relevant metrics such as waking after sleep onset (WASO) and sleep efficiency 107 .…”
Section: Conventional Sleep Classification Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that Random Forests, XGBoost and SVMs can be used efficiently for a variety of bioinformatics problems (Mall et al, 2017;Rawi et al, 2018;Mall et al, 2018;Ullah et al, 2018;Palotti et al, 2019;Elbasir et al, 2020).…”
Section: Traditional Machine Learning Modelsmentioning
confidence: 99%